Regulating Market Risk in Banks : The Options - Stephanou, Constantinos (World Bank, Washington, DC, 2012)
Regulators concerned about the costs of bank insolvency and of systemic risk arising from the volatility of bank trading portfolios have developed three different approaches to setting risk-based minimum capital adequacy standards for market risk. The author evaluates those three approaches--building blocs, internal models, and precommitment--and assesses their possible implications for bank capital, competition, and pricing decisions.